EFFICACY OF DIFFERENT CONCENTRATIONS OF CALCIFEROL (VIT D2) AGAINST MUS MUSCULUS - MATHUR, S.; SAXENA, Y. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1991)
No choice feeding test was carried out in the laboratory to evaluate the efficacy of calciferol at different concentrations (0.025, 0.05 & 0.1 percent) against M. musculus. It was observed that higher concentration 0.1% resulted in cent percent mortality after one day feeding with mean days to death being 2.1 where as 0.05% yielded 100 percent kill after three days of feeding and 0.025% yielded 50 percent mortality with mean days to death being 2.6 and 7.0 respectively. The symptoms of illness observed were sluggishness, pulmonary distress, polyurea and loss in weight.